2021
DOI: 10.1021/acsami.1c05191
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Transport across Metal/β-Ga2O3 Interfaces

Abstract: In this work, we study the thermal transport at β-Ga2O3/metal interfaces, which play important roles in heat dissipation and as electrical contacts in β-Ga2O3 devices. A theoretical Landauer approach was used to model and elucidate the factors that impact the thermal transport at these interfaces. Experimental measurements using time-domain thermoreflectance (TDTR) provided data for the thermal boundary conductance (TBC) between β-Ga2O3 and a range of metals used to create both Schottky and ohmic electrical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Many prior experimental studies have reached the opposite conclusion and reported that vibrational similarity between two materials is an important governor of thermal interface conductance. 14 , 30 32 (Reference ( 33 ) is an exception to this trend and reaches conclusions about the effect of vibrational similarity that are similar to the current study.)…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Many prior experimental studies have reached the opposite conclusion and reported that vibrational similarity between two materials is an important governor of thermal interface conductance. 14 , 30 32 (Reference ( 33 ) is an exception to this trend and reaches conclusions about the effect of vibrational similarity that are similar to the current study.)…”
Section: Resultssupporting
confidence: 86%
“…A number of experimental studies have explained experimentally observed trends for G in metal/insulator systems as a consequence of vibrational overlap between the metal and insulator. 14 , 35 , 37…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The metal/dielectric interfaces widely exist in complementary metal‐oxide semiconductor transistors, [ 84 ] in form of van der Waals force. In the work of Shi et al., [ 85 ] the ITCs at different metal/β‐Ga 2 O 3 interfaces were measured by TDTR. The experimental results were 31.2, 17.4, 82.7, and 81.7 MW m −2 K −1 for Au/β‐Ga 2 O 3 , Ti/β‐Ga 2 O 3 , Ni/β‐Ga 2 O 3 , and Al/β‐Ga 2 O 3 , respectively.…”
Section: Influence Factorsmentioning
confidence: 99%